Penggunaan Bahan Inkonvensional Sebagai Sumber Bahan Pakan - Isharyudono, Kelik; Mar'ah, Isna; Jufriyah, J (Laboratorium Bio Teknologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2019)
The availability of commonly used feed ingredients currently decreases production. This is due to the limited land that has begun to be degraded so that agricultural yields also decline. For this reason, it is necessary to look for other alternatives from the source of raw materials for feed in addition to common ingredients. The use of alternative (unconventional) feed ingredients is constrained by the limited data from the analysis of its chemical composition. In this study a table of feed ingredients composition has not been listed in the table of pre-existing feed composition. The aim is to provide information to the public about the content of unconventional materials that do not yet exist in the composition table. Thus it can be a reference to be used as a constituent component of rations. The test method used is the proximate analysis of the Weendee method. The test parameters included water content, ash content, crude fat content, crude fiber content and crude protein content. From the results of this study, several conventional materials have not been included in the composition table